2017
DOI: 10.1111/jsap.12680
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and ultrasonographic findings of the spleen and abdominal lymph nodes in healthy domestic ferrets

Abstract: The information provided in this study may act as a baseline for evaluation of the spleen and lymph nodes in ferrets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The abdominal cavity has multiple small lymph nodes. There is a single palpable lymph node (known as the jejunal lymph node or cranial mesenteric lymph node) (Suran et al 2017) in the mesentery that has been studied (Paul-Murphy et al 1999) and is consistent with the one found in minks. It is located at the junction of the cranial and caudal mesenteric veins and embedded in fat at the root of the small intestine mesentery, with the size in young adult ferrets being 12.4 ± 2.4 mm in length by 6.9 ± 2.0 mm in width (Paul-Murphy et al 1999).…”
Section: Lymph Nodes and Tonsilssupporting
confidence: 68%
See 2 more Smart Citations
“…The abdominal cavity has multiple small lymph nodes. There is a single palpable lymph node (known as the jejunal lymph node or cranial mesenteric lymph node) (Suran et al 2017) in the mesentery that has been studied (Paul-Murphy et al 1999) and is consistent with the one found in minks. It is located at the junction of the cranial and caudal mesenteric veins and embedded in fat at the root of the small intestine mesentery, with the size in young adult ferrets being 12.4 ± 2.4 mm in length by 6.9 ± 2.0 mm in width (Paul-Murphy et al 1999).…”
Section: Lymph Nodes and Tonsilssupporting
confidence: 68%
“…In a later study (Garcia et al 2011), the pancreaticoduodenal (5.29 ± 1.32 mm in length), splenic (5.93 ± 1.59 mm in length), gastric (7.7 ± 2.6 mm in length) and hepatic lymph nodes were identified in ferrets with average age of 3 years. Additional lymph nodes were later identified using ultrasound; specifically, the caudal mesenteric, medial iliac and lumbar aortic nodes (Suran et al 2017). Abdominal lymph node enlargement is common in ferrets with gastrointestinal disease, lymphosarcoma or chronic exposure to enteric coronavirus referred to as reactive lymphadenopathy, especially in older ferrets (Paul-Murphy et al 1999;Mayer et al 2014;Suran et al 2017).…”
Section: Lymph Nodes and Tonsilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower extremity vascular diseases in patients with diabetes mellitus generally cannot be detected clinically in the early stages due to the common complications of neuropathy [ 2 , 3 ]. Patients with diabetes mellitus usually are unaware of the fact that the early progress of lower extremity vascular disease is due to the loss of pain and the decreasing frequency of intermittent claudication, until the symptoms get worsen and the disease turns into an ulcer or gangrene, which usually occurs at the last stage of the lower extremity vascular disease and eventually leads to amputation [ 4 , 5 ]. Therefore, the early diagnosis and treatment of diabetes patients requires the index of early lower extremity vascular disease, which helps in avoiding amputation and in improving the living quality of patients [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%